A feasibility study into the measurement of physical activity levels of adults with intellectual disabilities using accelerometers and the International Physical Activity Questionnaire. (June 2017) - Dairo, Yetunde M.; Collett, Johnny; Dawes, Helen
Abstract : Accessible summary: Most physical activity (PA) studies exclude individuals with severe and profound intellectual disabilities, and the reasons for these exclusions are unclear. Therefore, this study explored the practicalities of recruiting and measuring adults with intellectual disabilities, including those with severe and profound intellectual disabilities. Each individual and their carer or family filled in a questionnaire where they were asked about their PA over the previous 7 days; thereafter, they were given an accelerometer for 7 days to measure their physical activities. Four things were found to be important for this type of study: (i) where participants lived; (ii) what was used in measuring their PA; (iii) their reported PA was similar to what their family/carer reported; and (iv) it was also similar to what was measured. The study showed that it is possible to measure PA irrespective of the intellectual disability severity and that adults with intellectual disabilities can tell you about their PA and so can their relatives/carers without the need for expensive equipment. Abstract: Background: Few studies have measured physical activity (PA) levels of adults with intellectual disabilities using both objective and subjective methods, but none included individuals with profound intellectual disabilities. To inform effective measurement of PA across the disability spectrum, this study explored: the feasibility of measuring PA levels using the International Physical Activity Questionnaire‐short version (IPAQ‐s) and a wrist‐worn 7‐day accelerometer; examined the level of agreement between instruments/raters; and established the recruitment rate. From the literature reviewed, no study has investigated these issues. Materials and Methods: Two‐hundred adults with intellectual disabilities from a local authority lists in UK were invited to participate. Participants were administered an accelerometer for seven days and the IPAQ‐s (self and carer‐reported). Results: Twenty participants with mild to profound intellectual disabilities (20–70 years) were recruited. The response rate was significantly different between home (16%) and residential homes (4%): χ 2 (1) = 7.7, p < .05. All participants completed the IPAQ‐s but only 15 completed 7‐day accelerometer. Self and carer‐reported PA had perfect agreement on IPAQ‐s, and agreements between instruments using PA guidelines was substantial ( k = 0.6, p < .05). However, mean moderate‐vigorous PA min/week differed between measures at 145 and 207 from IPAQ‐s and accelerometer respectively. Conclusions: Recruitment demonstrated a need for better engagement with residential homes. While both the IPAQ‐s and accelerometers can be used to evaluate PA levels, the IPAQ‐s was more acceptable and carer report was accurate, but it underestimated absolute moderate‐vigorous PA levels. These findings indicate that IPAQ‐s can be used to measure PA levels, including in those with profound intellectual disabilities.